2008
DOI: 10.1103/physrevb.78.174406
|View full text |Cite
|
Sign up to set email alerts
|

Near-zero-moment ferromagnetism in the semiconductor SmN

Abstract: The magnetic behavior of SmN has been investigated in stoichiometric polycrystalline films. All samples show ferromagnetic order with Curie temperature ͑T C ͒ of 27Ϯ 3 K, evidenced by the occurrence of hysteresis below T C . The ferromagnetic state is characterized by a very small moment and a large coercive field, exceeding even the maximum applied field of 6 T below about 15 K. The residual magnetization at 2 K, measured after cooling in the maximum field, is 0.035 B per Sm. Such a remarkably small moment re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
71
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 22 publications
9
71
2
Order By: Relevance
“…Using a parallel development of experimental and theoretical work, we have recently shown that GdN is a small gap semiconductor with potentially spin polarized carriers [3,4]. Subsequently, we have found that DyN and SmN are also ferromagnetic semiconductors in their ground states [5,6]. In the present paper we describe the magnetic properties of ErN films.…”
Section: Introductionmentioning
confidence: 92%
“…Using a parallel development of experimental and theoretical work, we have recently shown that GdN is a small gap semiconductor with potentially spin polarized carriers [3,4]. Subsequently, we have found that DyN and SmN are also ferromagnetic semiconductors in their ground states [5,6]. In the present paper we describe the magnetic properties of ErN films.…”
Section: Introductionmentioning
confidence: 92%
“…Experiment has shown the magnetisation of SmN is close to extinguished by this opposition. A value of 0.03 µ B per Sm 3+ ion is found that is furthermore dominated by the orbital contribution [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research into SmN has been driven by two main considerations; its potential for spintronic applications and its vanishingly small ferromagnetic moment. It is a member of the rare-earth nitride series, a group of materials owing their promise for spintronic applications to their status as intrinsic ferromagnetic semiconductors [1][2][3][4][5][6][7][8][9][10]. SmN is especially unique among the series, with a vanishingly small ordered moment arising from the near-cancellation of spin and orbital moments [4,5] fixed antiparallel by strong spin-orbit coupling.…”
Section: Introductionmentioning
confidence: 99%
“…It is a member of the rare-earth nitride series, a group of materials owing their promise for spintronic applications to their status as intrinsic ferromagnetic semiconductors [1][2][3][4][5][6][7][8][9][10]. SmN is especially unique among the series, with a vanishingly small ordered moment arising from the near-cancellation of spin and orbital moments [4,5] fixed antiparallel by strong spin-orbit coupling. So far the spintronic potential of the RENs remains largely untapped, though GdN has been integrated within spinfilters [11,12] and field effect transistors [13] while DyN has been incorporated into a magnetic tunnel junction [14].…”
Section: Introductionmentioning
confidence: 99%